Smart Library Mobile: Technology Collaboration in Improving Library Information Accessbility - INSANIA, INSANIA PUTRI (UIN Raden Intan Lampung, 2025)
The rapid development of information technology has driven significant changes to libraries, from conventional libraries to digital libraries. These changes have made libraries more popular and accessible through various mobile library applications such as iPusnas, iJakarta, and University eLibrary. Mobile applications are software designed specifically to run on mobile devices, such as smartphones or tablets. The implementation of smart mobile libraries is still uneven due to suboptimal technological collaboration. This condition has the potential to cause these services to be displaced by other applications that are more attractive and easier to use. Therefore, this gap demands a more integrated technological solution. This study aims to analyze how technological collaboration in smart mobile libraries can improve accessibility, information utilization, and user experience. The research method used is a qualitative research method with a library research approach. Data was obtained from secondary sources such as books, scientific journals, academic articles, dissertations, and official documents. Data collection techniques were carried out through the selection of relevant, credible, and up-to-date literature. The triangulation used was triangulation from various sources. The results of the study show that technological collaboration is very effective in helping to improve library accessibility, especially through online catalog features that support user needs. The online catalog feature facilitates real-time collection searches because it is integrated with the library system. In conclusion, the integration of digital library systems has an impact on improving accessibility in libraries, both in terms of ease of searching for information, flexibility of time and place, and service efficiency. Therefore, mobile libraries play an important role in improving the accessibility of library use and have the potential to become the main foundation for the development of more modern digital library services.